Faith in moderation : Islamist parties in Jordan and Yemen - Schwedler, Jillian (Cambridge University Press, 2006)
"Does political inclusion produce ideological moderation? Jillian Schwedler argues that examining political behavior alone provides insufficient evidence of moderation because it leaves open the possibility that political actors might act as if they are moderate while harboring radical agendas. Through a comparative study of the Islamic Action Front (IAF) party in Jordan and the Islah party in Yemen, she argues that the IAF has become more moderate through participation in pluralist political processes, while the Islah party has not. The variation is explained in part by internal group organization and decision-making processes, but particularly by the ways in which the IAF has been able to justify its new pluralist practices on Islamic terms while the Islah party has not. Based on nearly four years of field research in Jordan and Yemen, Schwedler contributes both a new theory of ideological moderation and substantial new detail about the internal workings of these two powerful Islamist political parties."--Jacket